Degos-like lesions in association with connective tissue diseases: A report of three cases and literature review - Taptim Stavorn (2020)
© 2019 Stavorn and Chanprapaph. Degos disease is characterized by atrophic porcelain-white papules with peripheral erythema. Degos-like lesions have been reported in association with several connective tissue diseases (CTDs), mostly systemic lupus erythematosus (SLE), and rarely in dermatomyositis and systemic sclerosis. Herein, we report three cases of Degos-like lesions in CTDs. Two cases had Degos-like lesions linked to dermatomyositis. Both cases presented with severe inflammatory myopathy without pathognomonic cutaneous signs for dermatomyositis and lacked myositis-specific autoantibodies. Our third case, to our knowledge, is the first case of Degos-like lesions in association with overlapping systemic sclerosis and SLE without major organ involvement. The clinical presentation and histopathology findings of our cases support that Degos-like lesions may not be a specific entity but can be considered as a unique clinical pattern expressed in patients with CTDs.